Neutrophil-to-lymphocyte ratio and monocyte-to-lymphocyte ratio predict length of hospital stay in myocarditis - Moritz Mirna; Lukas Schmutzler; Albert Topf; Uta C. Hoppe; Michael Lichtenauer (Scientific Reports, 2021)
Abstract Neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte ratio (MLR) are associated with the severity of various diseases. The aim of this study was to demonstrate the relationship of NLR and MLR with the severity of myocarditis. 202 consecutive patients with myocarditis were retrospectively enrolled in this study. Laboratory parameters and clinical data were extracted from hospital records and discharge letters. Median NLR was 2.48 (IQR 1.55–4.58) and median MLR was 0.42 (IQR 0.39–0.58). NLR and MLR correlated with HF, CRP and leukocyte count, MLR further correlated inversely with LV systolic function (rs = − 0.379, p = 0.030). Both ratios correlated better with length of hospital stay (NLR: rs = 0.435, p = 0.003; MLR: rs = 0.534, p < 0.0001) than CRP, leukocyte count, IL-6 or procalcitonin. AUCs for the prediction of prolonged hospital stay (NLR = 0.75, MLR = 0.80), and optimal cut-offs therefor were calculated. Patients who had in-hospital complications showed a higher NLR, however, this remained statistically insignificant. NLR and MLR correlated with the length of stay, as well as with several clinical and laboratory parameters in patients with myocarditis. Since white blood cell differentials are relatively easy and fast to perform, both ratios could facilitate further risk stratification in affected patients.